Short-Term Vs. Long-Term Glucocorticoids in COPD Exacerbation: A Comparative Efficacy Study - Muhammad Israr, Zia Ul Haq, Muhammad Shabbir, Jahangir Khan, Muhammad Kashif Khan, Hina Bukhari (Pakistan Journal of Medical & Health Sciences, 2023)
The current study aims to evaluate the comparative efficacy of short-term and long-term glucocorticoid treatment in patients with COPD exacerbation. A randomized clinical trial will compare the effectiveness of short-term and long-term glucocorticoid treatments in COPD exacerbation. One hundred ninety patients will be recruited and randomized into two groups: a short-term glucocorticoid group and a long-term glucocorticoid group. The primary outcomes will be assessed at the end of the treatment period to determine the efficacy of the treatments. Secondary effects will include quality of life, length of hospitalization, and adverse events. The results of this study will provide insight into the comparative efficacy of short-term and long-term glucocorticoid treatments in COPD exacerbation. Objective: Comparative efficacy of short-term (5-days) versus long-term (10-days) glucocorticoids at equivalent doses in managing COPD patients with acute exacerbations. Materials and Methods: Pakistan Institute of Medical Sciences (PIMS), Islamabad, conducted this randomized clinical trial in the inpatient pulmonology department. This research took six months following ethical clearance. The experiment included 190 patients in two groups of 95. Patients in the two groups were randomly administered Tab—prednisolone 5mg (40mg/24 Hours) for five days or ten days. Using a carefully constructed pro-forma, postgraduate residents gathered data on five parameters (FEV1, FEV1/FVC, Arterial Blood Gases, mMRC Dyspnoea Scale, Sputum color and amount, presentation with identical symptoms within 30 days following discharge). Results: Patients averaged 58.13 ± 11.12. Long-term patients were 58.34 ± 11.53 years old, whereas short-term patients were 57.93 ± 10.752. The short-term group included 86 (90.53%) male and 9 (9.47%) female cases, whereas the long-term group had 89 (93.68%) male and 6 (6.32%) female cases. Sputum color was normal in all groups after therapy. Short-term and long-term therapy groups had mean FEV1 changes of 8.12±4.85 and 7.14± 1.75, respectively. Following treatment, short-term mMRC was significantly lower (2.14±0.32) than long-term (2.73±0.44), with p-value < 0.001. The short-term group mMRC mean change was 1.67±0.53 compared to the long-term group 1.07±0.26, p-value < 0.001. Sputum amounts changed by 2.63 ± 1.67 in the short-term and 2.49 ± 0.72 in the long-term groups. Both groups had similar mean sputum quantities before, after, and after treatment, with a p-value > 0.05. Both groups had the same ABG parameter mean change following therapy. One month after discharge, neither group relapsed. Conclusion: The efficacy of short-term (5-days) glucocorticoids is better than long-term (10-days) glucocorticoids at equivalent doses in terms of mMRC reduction. At the same time, the therapeutic effect was statistically the same in both groups regarding improvement in FEV1, sputum color, sputum quantity, all parameters of ABGs, and relapse rates. Keywords: COPD, exacerbation, glucocorticoids, efficacy